Harmonizing religion and health: an exploration of religious reasons for defaulting ARVs among people living with HIV and AIDS in Gweru, Zimbabwe - Mutambara, Julia; Sodi, Tholene; Mtemeri, Joefrey; Makomo, Marcia (Routledge, 2021)
There has been a proliferation of faith healing organizations in Zimbabwe in the past decade. These organizations have been attracting many people especially those with chronic conditions as their leaders claim to have spiritual powers to heal illnesses. This has led to people with chronic conditions opting for spiritual healing over medical methods thereby defaulting ARVs. This qualitative study sought to explore religious related reasons that have led to defaulting Antiretroviral drugs (ARVs) among People Living with HIV and AIDS in Gweru, Zimbabwe (PLWHIV). Fifteen participants who at one point defaulted medications, six counselors and four religious leaders were interviewed. Content analysis was used to analyze data. Themes obtained revealed that PLWHIV defaulted medications because – they believed in faith healing, alternative medicines, perceived spirituality as the main cause of HIV and AIDS and that they had an allegiance to church values. The study recommends the need to provide HIV and AIDS education to leaders of religious organizations so as to harmonize religion and HIV and AIDS treatment.